2003
DOI: 10.1007/s00466-003-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the blockage ratio on the flow in a channel with a built-in square cylinder

Abstract: The structures wakes behind a square cylinder in a laminar channel flow is conducted numerically. The Strouhal number, drag and lift coefficients were studied in a periodic flow for different blockage ratios b ¼ 1=4; 1=6 and 1=8 at Reynolds number ranging from 62 to 300. The governing equations are solved by using control volume finite element method (CVFEM) adapted to the staggered grid. The SIMPLER algorithm is used for the velocitypressure coupling. The critical Reynolds numbers corresponding to the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
52
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 15 publications
17
52
1
1
Order By: Relevance
“…For the shedding behind the large cylinder the dominating peak gives f = 0.34 Hz for the experiments and f = 0.38 Hz for the simulations corresponding to Strouhal numbers St LDV = fD/U ∞ ≈ 0.234 and St CFD ≈ 0.262 which can be considered to be in good agreement. For the shedding behind the smaller cylinder the simulation gives the same frequency as behind the large cylinder whereas the LDV gives a peak at f = 0.6 Hz which is more consistent with other studies [37][38][39] behind fully-circular stepped cylinders. For the shedding behind the step, the experiments yield two dominant peaks, one at f = 0.36 Hz, which should correspond to the shedding from the large cylinder and f = 0.6 Hz which corresponds to the shedding from the small one, whereas the simulation once again gives the same frequency as for the large cylinder, not capturing the dynamics of the small cylinder or the step.…”
Section: Vortex Sheddingsupporting
confidence: 89%
See 1 more Smart Citation
“…For the shedding behind the large cylinder the dominating peak gives f = 0.34 Hz for the experiments and f = 0.38 Hz for the simulations corresponding to Strouhal numbers St LDV = fD/U ∞ ≈ 0.234 and St CFD ≈ 0.262 which can be considered to be in good agreement. For the shedding behind the smaller cylinder the simulation gives the same frequency as behind the large cylinder whereas the LDV gives a peak at f = 0.6 Hz which is more consistent with other studies [37][38][39] behind fully-circular stepped cylinders. For the shedding behind the step, the experiments yield two dominant peaks, one at f = 0.36 Hz, which should correspond to the shedding from the large cylinder and f = 0.6 Hz which corresponds to the shedding from the small one, whereas the simulation once again gives the same frequency as for the large cylinder, not capturing the dynamics of the small cylinder or the step.…”
Section: Vortex Sheddingsupporting
confidence: 89%
“…In addition, the effect of blockage on vortex shedding for the flow past a step cylinder can also be significant. Some previous studies [37,38,[40][41][42][43] have shown that the effect of channel blockage on vortex shedding for the flow past a step cylinder can also be significant as the channel blockage affects f, consequently influencing St. The increase of shedding frequency with the increase of the blockage ratios is evidently observed in these spectral results ( Figure 6).…”
Section: Vortex Sheddingsupporting
confidence: 50%
“…They investigated the effect of Reynolds number and shearing rate on drag forces and vortex-shedding. Turki et al [10] investigated the blockage ratio ( ) in their work. They showed that the data would be acceptable for ≤0.16 and would not be reliable for >0.25.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of blockage was investigated numerically by Stansby and Slaouti (1993), Anagnostopoulos et al (1996), Behr et al (1995) and Turki et al (2003). It is shown that, increasing the blockage factor leads to high Strouhal number, drag coefficient and stagnation pressure.…”
Section: Introductionmentioning
confidence: 99%